ANALISIS FAKTOR INTERNAL DAN EKTERNAL YANG MEMPERNGARUHI KAPASITAS UMKM KULINER DI KOTA KENDARI: STUDI KASUS UMKM BAWANG GORENG TUNGGALA - Jhon Labo; Iskandar Zainuddin Rela; Megafirmawanti Lasinta (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
The capacity of Micro, Small, and Medium Enterprises (MSMEs) is a critical factor that determines a business's ability to manage resources, enhance competitiveness, and maintain business sustainability amid an increasingly dynamic business environment. The development of MSME capacity is influenced by a combination of internal and external factors. The present study aims to analyse the internal and external factors affecting the capacity of culinary MSMEs in Kendari City, using the Tunggala Fried Onion MSME as a case study. The research employs a qualitative approach, adopting a case study design. The present study involved a total of 20 informants, consisting of one key informant and 19 primary informants. The selection of these informants was conducted using purposive sampling. The data were collected through a variety of methods, including observation, in-depth interviews, documentation, and a comprehensive literature review. The analysis was conducted using the Miles and Huberman interactive model, which includes data collection, data reduction, data presentation, and drawing conclusions. The validity of the data was established through the implementation of source triangulation and methodological triangulation. The research results indicate that the capacity of the Tunggala Fried Onion SME is classified as developed and adaptive, as demonstrated by the business’s ability to maintain sustainability for more than eight years, improve production quality and quantity, expand its marketing network, adopt digital technology, and build institutional networks that support business development. Internal factors influencing the SME’s capacity include human resources, financial management, production systems, and marketing. The human resources possess good production experience and skills, although they still face limitations in digital literacy. Structured financial management, standardized production processes, and marketing strategies that combine conventional and digital marketing further strengthen the business’s capacity. Meanwhile, external factors influencing the capacity of MSMEs include technology, government support, socioeconomic conditions, and the role of supporting institutions. The use of production technology and marketing digitization improves efficiency and market access, while government support, conducive socioeconomic conditions, and assistance from relevant institutions contribute to strengthening business capacity. Enhancing the capacity of MSMEs requires synergy between internal and external factors to support the sustainability and competitiveness of businesses over the long term.